Σημείωμα σχετικά με την πρόσφατη έκδοση του φιρμανιού της μονής Παντοκράτορος Αγίου Όρους του έτους 1569 - ΚΟΛΟΒΟΣ, Ηλίας; ΚΟΤΖΑΓΕΩΡΓΗΣ, Φωκίων (Byzantina Symmeikta, 2024)
The paper gives a completely revised edition and translation of a firman from the archive of the Athonite Monastery of Pantokrator, which has been recently published by J. Niehoff-Panagiotides και A. Nikopoulos with essential mistakes in the reading and the transliteration from Ottoman Turkish, as well as in the translation in Greek. Beyond this, the paper discusses critically the interpretations suggested by J. Niehoff-Panagiotides και A. Nikopoulos, based on this document, concerning the confiscation of the ecclesiastical and monastic properties in the Ottoman Empire during the reign of Sultan Selim II, in 1568/69.